2019
DOI: 10.1016/j.jtauto.2019.100012
|View full text |Cite
|
Sign up to set email alerts
|

Insights of rheumatoid arthritis risk factors and associations

Abstract: Rheumatoid arthritis (RA) is a defective post-translational modification of citrullinated peptides which cause synovial inflammation in joints. The present review elaborates the basic mechanisms of RA and the root causes of molecular mechanisms. The gender-based differentiation and probabilitiesof RA causes were discussed. Many report studies supporting that females are more prone to RA than males maybe suspected that circulating estrogen hormones 16a-hydroxy estrone, 2-hydroxy estrogens involvement in the RA … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
11
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 18 publications
(11 citation statements)
references
References 56 publications
0
11
0
Order By: Relevance
“…Given its rapid progression, low compliance rate, high disability rate, and many other characteristics, it can seriously affect people's normal work and life. The incidence of RA with deficiency of both qi and yin is increasing year by year (28,29). Previous studies have shown that the expression of inflammatory factors IL-18, IL-1β, and TNF-α in articular cartilage cells of patients with RA due to deficiency of both qi and yin sharply increase (30).…”
Section: Discussionmentioning
confidence: 99%
“…Given its rapid progression, low compliance rate, high disability rate, and many other characteristics, it can seriously affect people's normal work and life. The incidence of RA with deficiency of both qi and yin is increasing year by year (28,29). Previous studies have shown that the expression of inflammatory factors IL-18, IL-1β, and TNF-α in articular cartilage cells of patients with RA due to deficiency of both qi and yin sharply increase (30).…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies have reported risk factors for rheumatoid arthritis, such as sex, age, heredity, smoking, exposure to particles of asbestos and silica, and obesity [ 20 , 51 ]. In this study, we explored risk factors for rheumatoid arthritis in Tsarang residents by conducting linear multiple regression analysis using the ACR/EULAR 2010 score, which is a classification standard for rheumatoid arthritis, as the objective variable.…”
Section: Discussionmentioning
confidence: 99%
“…RA is a typical chronic systemic autoimmune disease dominated by inflammatory synovitis. Genetics, smoking, air pollution, and gender are all considered risk factors for RA ( 78 , 79 ). Its pathogenesis is complex, and pro-inflammatory factors such as interleukin (IL)-1, IL-17, IL-22, tumor necrosis factor alpha (TNF-α), IL-6, and matrix metalloproteinase (MMP) have been confirmed to be related to the development of RA ( 80 84 ).…”
Section: Lncrna and Ramentioning
confidence: 99%